(untitled) (Acta Polytechnica CTU Proceedings, 2017)
Friction buffer stops are the favoured construction of buffer stop, mainly due to its high resistance and variety of layout. Last but not least is its manner of deceleration induced upon impact and during the braking what makes it smart solution in railway transport safety. The general approach of designing buffer stops is via usage of the kinetic energy and its conversion into work. Paper describes input parameters such as train velocity or buffer stop vicinity which is expressed by the safety coefficient implanted within the calculation. Furthermore, the paper shows the principle of calculation the friction buffer stop work, or to be more precise, the work of its braking jaws and optionally the work of additional braking jaws located behind the buffer stop. Last section of the paper is focused on the examples of designing friction buffer stops, points out the main complications and shows the charts of relation amongst braking distance, kinetic energy and braking force and the charts of relation between deceleration rate and braking distance.